Dental Caries Diagnosis, Prevention and Management - Akarslan, Zühre (Dentistry, 2018)
This book provides information to the readers starting with the history of oral hygiene manners, and modern oral hygiene practices. It continues with the prevalence and etiology of caries and remedy of caries through natural sources. Etiology of secondary caries in prosthetic restorations and the relationship between orthodontic treatment and caries is addressed. An update of early childhood caries is presented. The use of visual-tactile method, radiography and fluorescence in caries detection is given. The book finishes with methods used for the prevention of white spot lesions and management of caries.